An Overview of Geological Education in Australia - Watkins JR (The Australasian Institute of Mining and Metallurgy, 1986)
The educational system is a dynamic; a flow resource that can be significantly shaped, changed and - refined by educationists. This paper analyses these various facets of geo- science education in Australia. The Australian educational philosophy is essentially a laissez- faire model, a free market approach without any real government or professional directive or stratagem. Students are therefore free to choose their own educational pathway dependent only upon their ability and the access to courses. Geological education at the tertiary level in Australia is described and critically analysed. There is a real need for a rationalisation of geological education in Australia, and this rationalisation should include not only the number of courses offered but should also aim to fully define both the philosophy and purpose of geological education and the accreditation procedures for the Students.